Brasile, terra del futuro - Campani, Giovanna (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The short note represents a travel “journal”, prepared between the end of October 2020 and the end of January 2021, in the Brazilian state of Ceará and in Rio de Janeiro. It includes brief descriptions of glimpses of everyday life, in the vague search for an anthropological gaze; reflections or rather attempts to develop an embryonic analysis; confused evocations of feelings and memories. The pandemic cannot be ignored, but the note shows how social distancing cannot occur in Brazilian society. Despite this, Brazil does not have a higher number of deaths than European countries, but lower.